PENGARUH CITRA AYU TING TING SEBAGAI BRAND AMBASSADOR IKLAN REXONA DEO LOTION DALAM KEPUTUSAN PEMBELIAN DI DESA KARANGAN, TRENGGALEK - Arisanti, Riska; Zulaikha, Zulaikha (Fakultas Ilmu Komunikasi Universitas dr. Soetomo, 2019)
In an increasingly modern era like now, business competition that occurs between one company and another is increasingly dynamic, complex and presents various challenges that must be faced by the company to capture and maintain market share. Taking top celebrities to become brand ambassadors or advertising stars is an effective way to increase purchases. Ayu Ting Ting, with all her popularity and controversy, has collaborated with Rexona to become a star ambassador for Rexona deolotion products. The image of a brand ambassador becomes one of the considerations in choosing a brand ambassador. A positive self-quality image and public trust from a celebrity who is an advertisement star or brand ambassador will further obscure the advertising products that star in it. The theory used in this study is communication theory, marketing communication, advertising, theory brand ambassadors, image and purchasing decisions. The method used in this study is quantitative research with the type of correlational quantitative research. The samples in this study were 100 female respondents in Karangan village of Trenggalek, with a range of ages between 17 to 25. From the results of statistical calculations, it was shown that there was a significant influence on the image of Ayu Ting Ting as a brand ambassador for Rexona Deolotion's advertisement on purchasing decisions in the Karangan village of Trenggalek.Keywords: image; purchasing decision